How do experiences in Iraq affect alcohol use among male UK armed forces personnel?. Issue 9 (4th January 2008) - Browne, T; Iversen, A; Hull, L; Workman, L; Barker, C; Horn, O; Jones, M; Murphy, D; Greenberg, N; Rona, R; Hotopf, M; Wessely, S; et al.
Abstract : Objectives: This paper reports on a statistically significant association between alcohol use and deployment to the 2003 Iraq War. It assesses the occupational factors and deployment experiences associated with heavy drinking in regular UK servicemen deployed to Iraq in the first phase of the 2003 Iraq War (Operation TELIC 1, the military codename for the conflict in Iraq). Methods: A random representative sample of 3578 regular male UK Armed Forces personnel who were deployed to Iraq during Operation TELIC 1 participated in a cross-sectional postal questionnaire study (response rate 61%). Participants completed a questionnaire, between June 2004 and March 2006 (ie, after deployment), about their health, including a measure of alcohol use (Alcohol Use Disorders Identification Test, AUDIT) and questions about their experiences on deployment to Iraq. Heavy drinkers were identified as those scoring 16 or above on the AUDIT. Results: After adjustment for sociodemographic and military factors, and the presence of psychological distress, heavy drinkers were more likely to have had major problems at home during (odds ratio (OR) 1.33, 95% confidence interval (CI) 1.04 to 1.70) and following their deployment (OR 1.68, 95% CI 1.32 to 2.14). Being deployed with their parent unit (OR 1.28, 95% CI 1.02 to 1.61), medium to high in-theatre unit comradeship (medium: OR 1.35, 95% CI 1.04 to 1.77; high: OR 1.35, 95% CI 1.02 to 1.79) and poor unit leadership (OR 1.78, 95% CI 1.37 to 2.31) were also associated with heavy drinking. Conclusions: Deployment experiences and problems at home during and following deployment, as well as the occupational milieu of the unit, influence personnel's risk of heavy drinking.